Atitude perante o sofrimento e a percepção do sentido da vida: um estudo entre católicos, evangélicos e praticantes do budismo - Silva, Monique Suelen Gabriel da (2014)
Suffering is a human condition that is linked to the search for meaning. From this perspective, religions have, in general, a worldview that encompasses both the meaning of life and the meaning of suffering. In this sense, the present work had as main objective to construct and validate an instrument on Attitude Towards Suffering and ascertain the relationship between the attitude towards the suffering and the perception of the meaning of life according to three religious groups: Buddhists, Catholics and Evangelicals. For this purpose, we conducted two studies. The study 1 was composed of 319 participants of both sexes with a mean age of 27.07 years. As instruments for data collection was built Questionnaire Attitude Towards Suffering (QATS) and a Socio-demographic Questionnaire. We carried out a factor analysis of the principal axes with varimax rotation, the results of this extraction suggest the presence of two factors: positive attitude towards suffering and negative attitude towards the suffering, with Cronbach's Alpha, respectively, 0.84 and 0.64. Study 2 was composed of 113 participants of both sexes, with 53 practitioners of Buddhism and 60 Christians (30 Catholics and Evangelicals 30), with an average of 37.3 years. In addition to the scales used in study 1, was added Meaning in Life Questionnaire Meaning in Life Questionnaire (MLQ). An association between the presence of Sense and Positive Attitude Towards Suffering (r = 0.21, p <0.03) was observed and a negative correlation between the search for meaning and fulfillment (r = - 0.34, p <0.0001). Regarding the positive attitude towards the suffering it was found that the average among Catholics, Evangelicals and practitioners of Buddhism differ from each other with respect to Negative Attitude, neither significant difference was observed between the means of the groups studied. These results are discussed in light of the existential analysis of Viktor Frankl